Hardware-software complex for automated control and monitoring of the vacuum system of the coating setup "Bulat-6" - Gubarev, S.P.; Leonovych, A.V.; Muratov, R.M.; Nezovibat'ko, Y.N.; Opaleva, G.P.; Taran, V.S.; Zolototrubova, M.I. (Вопросы атомной науки и техники, 2019)
The hardware-software complex for automated control and monitoring of the vacuum system of the coating setup "Bulat-6" is presented. Its use provides the stability of the process of obtaining and maintaining the required vacuum in the plant. The complex is built on the basis of the software-logic controller (PLC) type ELC-22 XLogic.